Biblical women and the arts - Clines, David J. A.; Exum, J. Cheryl; Apostolos-Cappadona, Diane (Biblical reception, 2018)
"In this guest-edited issue of Biblical Reception, edited by Diane Apostolos-Cappadona, contributors examine the reception of the bible in art. Most of the contributions focus on biblical women, or on encounters with women in the bible. The volume is roughly chronological in structure, beginning with two pieces on Eve, one of which compares representations of Eve with those of the Virgin Mary, the other which considers how Eve is presented in Islamic texts and images. Following a contribution on Esther and Sarah the volume moves on to consider New Testament texts, with notable focus on women at the peripheries of society (the woman with the hemorrhage in Mark's gospel and the woman of Samaria). Attention is also paid to representations of Mary Magdalene and of Judith and Salome. The volume concludes with a piece on apocalyptic imagery and the woman clothed with the sun of Revelation 12. Featuring over 50 high quality color images, this volume provides scholarship of the highest level on biblical art." --Bloomsburg Publishing